Internet of Things: An Experiment with Residential Automation for Robotics Classes - Bento, Antonio Carlos (International Research Journal of Management, IT & Social Sciences, 2018)
This study presents the results obtained in a technological and applied research for robotics disciplines, using the Internet of Things with the device Arduino Uno to automate the lights of a residence, to have the ease of control during the day to day, the panel of control is accessed by a browser software on a mobile phone or computer, providing greater convenience for people. During the research were analyzed the different devices available in the national market, the results allowed to conclude the development of a simple solution that could contribute to robotics classes, the main interest related to the results involves the application experience, which can be expanded according to with the need of the user and its environment, proposing new applications in disciplines that involve robotics, database, internet, programming and electronics.